Metaverse Marketing – The Future of Sustainable Marketing - MOISE, Daniel; DIACONU, Amelia; OANCEA NEGESCU, Mihaela Diana; DINU, Mihai (European Journal of Sustainable Development, 2023)
Society is evolving and even trying to “conquer” new universes, no matter if they are physical, virtual online. The CoVid-19 Pandemic, wars, natural catastrophes, are pushing humans to adopt and to spend more time in Metaverse platforms, as a means of escaping the ordinary and their daily problems. Where there are potential customers, companies, or organizations will follow in order to change the behavior and make them purchase products, or services, increase the brand awareness, or in the case of politicians, or politics, determine them to vote, or agree with the wanted strategies. Not only will the customers have avatars, as well as organizations are becoming more humane and attractive towards users. Organizations are investing in technologies related to AI (artificial intelligence) and technologies related to multiverse as the attractiveness of these virtual universes are more and more appealing. In this study, we are conducting research in order to discover what the benefits are, but also how brands, companies and organizations that are joining, use marketing strategies, policies and tactics to increase their sales. In the Metaverse platforms, there will not be only the place to spend leisure time, socialize, do the shopping, even working, or why not, even voting, there being practically no limits. We have discovered in this study that customers would also like some sort of regulations, which relate to how marketing and experiential marketing are conducted in Metaverse platforms. Like the Internet, the Metaverse has the power to drastically change economic and social life for all the parties involved. Keywords: Metaverse, marketing, experiential marketing, customer behavior, AI